The Role of Islamic Education in Building a Lifelong Learning Society - Moh. Miftachul Choiri (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
The concept of a lifelong learning society has become an essential demand in responding to the dynamics of social, cultural, and technological changes in the modern era. However, the implementation of lifelong learning within Islamic education still faces various challenges, such as an education paradigm that tends to be formalistic, limited pedagogical innovation, and the suboptimal role of Islamic educational institutions in fostering a culture of continuous learning. This study aims to analyze the role of Islamic education in building a lifelong learning society through a conceptual review and the values of Islamic education. This research employs a qualitative approach with a library research design. Data were collected through an extensive review of literature, including books, journal articles, and academic documents relevant to Islamic education and lifelong learning, and were analyzed using content analysis techniques. The findings indicate that Islamic education possesses strong philosophical foundations and values that support lifelong learning, such as the concept of learning as an act of worship, the balance between knowledge, morality, and practice, and the internalization of values such as tawhid (monotheism), sincerity, trustworthiness, and ijtihad (intellectual endeavor). Islamic educational institutions, including pesantren, madrasah, and Islamic higher education institutions, play a strategic role as centers of formal and non-formal learning within society. The implications of this study emphasize the need to strengthen policies, promote pedagogical innovation, and utilize technology grounded in Islamic values in order to optimize the role of Islamic education in building a lifelong learning society.